Meiotic Crossover Control by Concerted Action of Rad51-Dmc1 in Homolog Template Bias and Robust Homeostatic Regulation - Lao, Jessica P.; Cloud, Veronica; Huang, Chu-Chun; Grubb, Jennifer; Thacker, Drew; Lee, Chih-Ying; Dresser, Michael E.; Hunter, Neil; Bishop, Douglas K. (PLoS genetics, 2013)
During meiosis, repair of programmed DNA double-strand breaks (DSBs) by recombination promotes pairing of homologous chromosomes and their connection by crossovers. Two DNA strand-exchange proteins, Rad51 and Dmc1, are required for meiotic recombination in many organisms. Studies in budding yeast imply that Rad51 acts to regulate Dmc1's strand exchange activity, while its own exchange activity is inhibited. However, in a dmc1 mutant, elimination of inhibitory factor, Hed1, activates Rad51's strand exchange activity and results in high levels of recombination without participation of Dmc1. Here we show that Rad51-mediated meiotic recombination is not subject to regulatory processes associated with high-fidelity chromosome segregation. These include homolog bias, a process that directs strand exchange between homologs rather than sister chromatids. Furthermore, activation of Rad51 does not effectively substitute for Dmc1's chromosome pairing activity, nor does it ensure formation of the obligate crossovers required for accurate homolog segregation. We further show that Dmc1's dominance in promoting strand exchange between homologs involves repression of Rad51's strand-exchange activity. This function of Dmc1 is independent of Hed1, but requires the meiotic kinase, Mek1. Hed1 makes a relatively minor contribution to homolog bias, but nonetheless this is important for normal morphogenesis of synaptonemal complexes and efficient crossing-over especially when DSB numbers are decreased. Super-resolution microscopy shows that Dmc1 also acts to organize discrete complexes of a Mek1 partner protein, Red1, into clusters along lateral elements of synaptonemal complexes; this activity may also contribute to homolog bias. Finally, we show that when interhomolog bias is defective, recombination is buffered by two feedback processes, one that increases the fraction of events that yields crossovers, and a second that we propose involves additional DSB formation in response to defective homolog interactions. Thus, robust crossover homeostasis is conferred by integrated regulation at initiation, strand-exchange and maturation steps of meiotic recombination.